Especulaciones de la vivienda y el urbanismo (2020)
In a world where more than half of the population lives in urban spaces, knowledge of the organization, growth, and hierarchical order that make up these spaces, has become one of the geographic facts of great interest, due to its political implications. , economic, social, cultural, spatial (Bottino, 2009). Certainly, most cities have been built based on the population’s needs for housing and urban spaces, however, for a few decades the personal, political and financial interests of many people have prevailed over the construction of a city, especially in residential and recreational spaces.